2005
DOI: 10.1055/s-2005-917078
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylaluminum (TMA)-Catalyzed Reaction of Alkynyllithiums with Ethylene Oxide: Increased Yields and Purity of Homopropargylic Alcohols

Abstract: An efficient protocol was developed to obtain homopropargylic alcohols. Subjecting alkynyllithiums and ethylene oxide to 10-20 mol% of trimethylaluminum provided homopropargylic alcohols in good yields.Successful completion of a synthesis of a natural product possessing moderate complexity typically requires the preparation of starting materials in gram quantities. The syntheses of these relatively simple and low molecular weight precursors are usually the least interesting in a synthetic sequence that may ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Protection of the acetylenic alcohol 13 afforded terminal alkyne 14 (95% yield), which was metalated with n -BuLi and quenched with excess ethylene oxide to give the two carbon homologated alcohol 15 in 75% yield. As reported earlier, 41 we also observed that ethylene oxide opening with lithium acetylides (e.g., TBDPSO(CH 2 ) 4 C≡CLi) in the presence of boron trifluoride etherate has low reproducibility, especially on large scale, and requires freshly distilled catalyst. Use of hexamethylphosphoramide, 42 which strongly coordinates to lithium cations, is a robust alternative to carry out this conversion.…”
Section: Resultssupporting
confidence: 78%
“…Protection of the acetylenic alcohol 13 afforded terminal alkyne 14 (95% yield), which was metalated with n -BuLi and quenched with excess ethylene oxide to give the two carbon homologated alcohol 15 in 75% yield. As reported earlier, 41 we also observed that ethylene oxide opening with lithium acetylides (e.g., TBDPSO(CH 2 ) 4 C≡CLi) in the presence of boron trifluoride etherate has low reproducibility, especially on large scale, and requires freshly distilled catalyst. Use of hexamethylphosphoramide, 42 which strongly coordinates to lithium cations, is a robust alternative to carry out this conversion.…”
Section: Resultssupporting
confidence: 78%
“…The method has been used in the synthesis of 6-nor-fluvirucinin B 1 (Scheme ), in the preparation of chiral building blocks having 1,3- syn -Me groups (Scheme ), and at the beginning of the syntheses of (−)-mycalamide A (Scheme ) and amphidinolide P (Scheme ) . Me 3 Al-catalyzed reactions of alkynyllithiums with oxirane have also been described …”
Section: Reactions Of Maas Involving Nucleophile Ligand Transfer Proc...mentioning
confidence: 99%
“…Once we found the proper base to use in the preparation of the Wittig reagent, the synthesis of the target started with the known terminal acetylene 12 , Scheme 23. Homopropargyl alcohol 13 was prepared following a procedure reported by Brummond 24. This procedure employs Me 3 Al as an additive in the ethylene oxide opening reaction and gives a reproducible yield of the desired product.…”
Section: Resultsmentioning
confidence: 99%